Riset Pemasaran dalam Mendukung Keberlanjutan Bisnis Bank Syariah - Muhammad Isa (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2016)
Today, marketing research is very important to do. An Islamic Banking Manager must collects more information to make the best decisions. The winner is who has the informations. A manager can get the factual informations about market by using marketing research. Marketing research has steps and doing by rulers. Marketing research must doing continuously to know the informations about opportunities and threats. A manager will make the best decision by use these informations.